Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, Michael; Jachura, M.; Brecht, Benjamin; Avenhaus, M.; Silberhorn, Christine (Physical Review A)

Absence of pressure sensitivity of apparent wall slip in pressure-driven flow of non-colloidal suspensions - Pieper, Sven; Kirchhoff, Nadine; Schmid, Hans-Joachim (Rheologica Acta)
We investigated an explanation for the length dependence of apparent wall slip in capillary and slit die experiments that had been implied in earlier studies. Firstly, we used a very long slit die fitted with six equidistant pressure transducers and an adjustable outlet. It was found that, all other parameters being equal, the impact of pressure on the flow behavior of suspensions was not different from the impact on the unfilled matrix fluid. Particle-related properties, such as apparent wall slip, were therefore not influenced by pressure as assumed by other authors. Secondly, we determined wall slip velocities by both the Mooney method and numerical simulation, based on an implementation of Phillips constitutive equation for particle migration. This led to a similar length dependence of wall slip as had been reported in an earlier work. We concluded that this was due to the transient nature of particle migration and its interrelationship with apparent wall slip, rather than an influence of pressure.